“Point of View” in Literary Criticism, History and History of Philosophy: Perspective of Dialogue - O. A. Vlasova (Научный диалог, 2020)
The problem of the point of view is considered, taking into account the vector of continuity from literary studies through history to the history of philosophy. The traditional approaches of the Anglo-American (G. James, P. Lubbock) and French (G. Genette) literary traditions are analyzed. The main terminology and methodological strategies that can be used in historical and historical-philosophical science are highlighted. It is demonstrated that within the framework of history, the terminology of focalization contributes to the accentuation of the figure of the researcher, who sets the conditions for the perception of historical material. Based on a critical analysis of the models of focalization proposed by A. Munslow in history, the main directions of rethinking the problem of  focalization in historical and historical-philosophical practice are determined. The specificity of posing the problem of point of view and focalization in the history of philosophy is characterized. It is emphasized that turning to it allows us to pose the problem of the relationship between history and modernity, history and philosophy. Such problematization of historical and philosophical practice is much more successful than traditional terminology, contributing to the comprehension of modern development trends. The study of the problem of point of view demonstrates the commonality of the methodological problems of the humanities (literary criticism, history, history of philosophy) and the need for a general humanitarian dialogue.